2021
DOI: 10.1177/21582440211006056
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Turkish Version of the Experiences in Close Relationships–Relationship Structures Questionnaire (ECR-RS)

Abstract: The aim of this study was to adapt the Turkish version of the Experiences in Close Relationships–Relationship Structures Questionnaire in a sample of Turkey. Study I was conducted to prove the reliability and validity of the results obtained as a result of the adaptation of the Experiences in Close Relationships–Relationship Structures (ECR-RS) Questionnaire to Turkish culture. The study showed that the Experiences in Close Relationships–Relationship Structures Questionnaire and its subscales were reliable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…and Turkish [21] . An advantage of ECR-RS over ECR and ECR-R is the fewer items which makes it feasible for For attachment with father also two factors emerged in EFA explaining 55.96% variance.…”
Section: Methodsmentioning
confidence: 99%
“…and Turkish [21] . An advantage of ECR-RS over ECR and ECR-R is the fewer items which makes it feasible for For attachment with father also two factors emerged in EFA explaining 55.96% variance.…”
Section: Methodsmentioning
confidence: 99%
“…The adaptation to different cultures of the nine-item ECR-RS has shown a good fit to the two-dimensional model in adults, adolescents, and children (Deveci Şirin & Şen Doğan, 2021). The Portu-guese (Moreira et al, 2015), Hungarian (Gyöngyvér & András, 2016), Czech (Siroňová et al, 2020), Swedish (Sarling et al, 2021), andTurkish (Deveci Şirin &Şen Doğan, 2021) versions have been validated in adults. Fewer adaptations have been made for adolescents and children (Karapas et al, 2015;Marci et al, 2019), but those published have demonstrated to follow the proposed two-dimensional model.…”
mentioning
confidence: 99%
“…Attachment anxiety refers to the degree to which people worry about others not being available when they are needed, whereas attachment avoidance represents the extent to which people feel uncomfortable with emotional dependency, closeness, and intimacy. Although each of these approaches is currently considered to respond to different objectives, recent literature maintains that the dimensional perspective offers a more adequate and accurate representation of the attachment domain (Deveci Şirin & Şen Doğan, 2021;Sarling et al, 2021).…”
mentioning
confidence: 99%